1992
DOI: 10.1584/jpestics.17.4_213
|View full text |Cite
|
Sign up to set email alerts
|

Lowered Virulence to Rice Plants and Decreased Biosynthesis of Gibberellins in Mutants of <i>Gibberella fujikuroi</i> Selected with Pefurazoate

Abstract: Mutants of Gibberella fujihuroi were obtained by selection from a large number of conidia of a wild type field isolate of the fungus on agar plates containing lethal concentration of a sterol demethylation inhibitor, pefurazoate.The mutants isolated from the colonies grown on the plates had higher minimal growth-inhibitory concentrations of pefurazoate and the EC95 values were higher than that for the mother isolate but only a small increase was observed in the EC5a values. Though the slope of the dosage-respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1994
1994
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…It has been reported that some DMIs inhibit the gibberellin production of F. fujikuroi. 2,18,19) Takenaka et al 20) reported that the less-sensitive mutants selected by pefurazoate showed low virulence to rice and low gibberellin production. They suggested the involvement of the enzyme component or factor for the demethylation of 24-methylenedihydrolanosterol in the pathway to ergosterol and kaurene oxidation steps in the pathway to gibberellins.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that some DMIs inhibit the gibberellin production of F. fujikuroi. 2,18,19) Takenaka et al 20) reported that the less-sensitive mutants selected by pefurazoate showed low virulence to rice and low gibberellin production. They suggested the involvement of the enzyme component or factor for the demethylation of 24-methylenedihydrolanosterol in the pathway to ergosterol and kaurene oxidation steps in the pathway to gibberellins.…”
Section: Discussionmentioning
confidence: 99%
“…An example in that direction is given by the unexpected phenotype of mutants resistant to pefurazoate, an inhibitor of sterol biosynthesis. The reduced capacity of these mutants to synthesise gibberellins (Takenaka et al, 1992) suggests a relation between a demethylation step in sterol biosynthesis and the oxidation ofkaurene in the gibberellin pathway.…”
Section: Gibberellin Mutantsmentioning
confidence: 98%
“…A regulatory connection between the two pathways seems unlikely, but both may be related indirectly, for example, by a common dependeance on enzymes and cofactors. This may explain that some inhibitors of one of the pathways are inhibitors of the other, and the reduced capacity to synthesize gibberellins of the mutants resistant to pefurazoate, an inhibitor of sterol biosynthesis [143].…”
Section: Relation Between the Synthesis Of Gibberellins And Other Termentioning
confidence: 99%